2016
DOI: 10.1002/pon.4064
|View full text |Cite
|
Sign up to set email alerts
|

Changes in social support predict emotional well-being in breast cancer survivors

Abstract: This study highlights the decline in social support among recently treated female breast cancer survivors and the importance of maintaining high-quality social support for emotional well-being. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 37 publications
2
100
0
7
Order By: Relevance
“…In breast cancer survivors, women who felt more lonely experienced greater depressive symptoms than those who felt more socially connected (Jaremka et al, , ). A recent study in this population found that social support quality was a significant predictor of increases in depression, stress and negative affect (Fong, Scarapicchia, McDonough, Wrosch, & Sabiston, ). Likewise, higher levels of social support have been found to be associated with better breast cancer survival (Kroenke et al, ), while lower levels are consistently associated with higher likelihoods of breast cancer‐specific and all‐cause mortality (Soler‐Vila, Kasl, & Jones, ; Weihs et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…In breast cancer survivors, women who felt more lonely experienced greater depressive symptoms than those who felt more socially connected (Jaremka et al, , ). A recent study in this population found that social support quality was a significant predictor of increases in depression, stress and negative affect (Fong, Scarapicchia, McDonough, Wrosch, & Sabiston, ). Likewise, higher levels of social support have been found to be associated with better breast cancer survival (Kroenke et al, ), while lower levels are consistently associated with higher likelihoods of breast cancer‐specific and all‐cause mortality (Soler‐Vila, Kasl, & Jones, ; Weihs et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…Physical activity (PA) can alleviate many of these challenges and improve quality of life . Social support may play an important role in rehabilitation from cancer because it is positively associated with PA and can assist in coping with cancer . Interventions often include opportunities for social interactions, such as group PA or peer support.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, social support not only alleviates stress but also improves the individual's coping ability [59] and provides psychological compensation for social conflicts or lack of relationships [60]. Neurobiological factors corroborate these results.…”
Section: Moderation Effect Of Formal and Informal Social Supportmentioning
confidence: 57%